2015
DOI: 10.1177/0022034515609268
|View full text |Cite
|
Sign up to set email alerts
|

ZO-1 and -2 Are Required for TRPV1-Modulated Paracellular Permeability

Abstract: The tight junction-based paracellular pathway plays an important role in saliva secretion. Zonula occludens (ZO) proteins are submembranous proteins of tight junction complex; however, their function in salivary epithelium is poorly understood. Here, we found that activation of transient receptor potential vanilloid subtype 1 (TRPV1) by capsaicin increased rat saliva secretion both in vivo and ex vivo. Meanwhile, TRPV1 activation enlarged the width of tight junctions between neighboring acinar cells, increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…Alteration of the transient receptor potential vanilloid subtype 1 (TRPV1) and muscarinic receptors is involved in functional and morphological changes early after transplantation. Administration of exogenous neurotransmitters, particularly carbachol and capsaicin, can improve early secretion after SMG transplantation [29][30][31][32][33][34][35][36][37] . Based on these findings, carbachol and capsaicin have been clinically used to regulate secretion of transplanted SMGs for prevention of duct obstruction due to minimal secretion during the ''latent period'' 29,30,38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Alteration of the transient receptor potential vanilloid subtype 1 (TRPV1) and muscarinic receptors is involved in functional and morphological changes early after transplantation. Administration of exogenous neurotransmitters, particularly carbachol and capsaicin, can improve early secretion after SMG transplantation [29][30][31][32][33][34][35][36][37] . Based on these findings, carbachol and capsaicin have been clinically used to regulate secretion of transplanted SMGs for prevention of duct obstruction due to minimal secretion during the ''latent period'' 29,30,38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, Rho kinase also exerts a strong effect on epithelial polarization. Li et al reported the inhibition of Rho kinase abolished correct distribution of tight junction proteins, potentially influencing saliva secretion given the role of tight junctions in paracellular transport of fluid [106]. The activated Rho kinase signaling pathway is also involved in the apoptosis of SG epithelial cells, and when in vitro cultured mouse SG stem cells were incubated with Y-27,632, expression of senescence-related proteins p16 and p21 was downregulated, and cellular proliferation was enhanced [107,108].…”
Section: Inhibitors Of Small Rho Gtpasesmentioning
confidence: 99%
“…For example, vitamin C deficiency downregulates the expression of TJ proteins in the gills of grass carp, including ZO-2, 61 and activation of the transient receptor potential vanilloid subtype 1 by capsaicin, an active component of chili peppers, increases the rate of saliva secretion by augmenting the paracellular permeability of submandibular gland cells through a mechanism that involves increased RhoA-ROCK signaling and ZO-1 and ZO-2 downregulation. 62 Moreover, in obesity-induced liver steatosis, high-fat diet-fed mice exhibit a reduced expression of ZO-1 and ZO-2 in the large bowel, and, although probiotic supplementation helps to maintain ZO-1 and ZO-2 expres-sion, it cannot be restored to the level present in chow-fed mice. 63 Similarly, treatment of endothelial cells with palmitate, one of the most abundant saturated fatty acids in plasma, which is substantially elevated following high-fat diet, induces the NLRP3 inflammasome complex and reduces endothelial expression of ZO-1 and ZO-2, leading to an increase in endothelial permeability.…”
Section: Factors That Regulate Zo-2 Expression At Tjsmentioning
confidence: 99%